PREVALENCE OF SMARTPHONE ADDICTION AND ASSOCIATED FACTORS AMONG HEALTH SCIENCES STUDENTS AT DAI NAM UNIVERSITY IN 2023 (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe the prevalence of smartphone addiction and identify associated factors among health sciences students at Dai Nam University in 2023.Subjects and Methods: A cross-sectional study was conducted among 447 undergraduate students from the Faculties of Medicine, Nursing, and Pharmacy at Dai Nam University, Hanoi, Vietnam. Data were collected using a structured self-administered questionnaire. Smartphone addiction was assessed using the Smartphone Addiction Scale – Short Version (SAS-SV). Descriptive statistics, Chi-square tests, and binary logistic regression analyses were performed using Stata 16.0.Results: The mean total SAS-SV score was 35.71 ± 8.88, ranging from 10 to 60 points. The highest mean score was observed for the item “I wouldn’t be able to stand not having a smartphone” (4.31 ± 1.40). Overall, 69.80% of participants were classified as having smartphone addiction. Smartphone addiction prevalence ranged from 64.91% to 79.63% across participant groups and was highest among second-year students (79.63%) and Nursing students (77.32%). Logistic regression analysis showed that students with other living arrangements had significantly lower odds of smartphone addiction compared with those living with family (OR = 0.22; 95% CI: 0.05–0.95; p = 0.043). No statistically significant associations were found for gender, year of study, place of birth, or academic major (p > 0.05).Conclusion: Smartphone addiction was highly prevalent among health sciences students at Dai Nam University. Psychological dependence on smartphones appeared common, highlighting the need for interventions promoting healthy smartphone use and supporting students’ mental health and academic performance.
Keywords: smartphone addiction, health sciences students, SAS-SV, university students, Vietnam.